TOPOGRAPHY AND HISTOLOGY OF PAROTID GLAND IN ONE HUMPED CAMEL - N. S.AL-Samarrae; F. 0. Rabie; T. A. Abbas (The Iraqi Journal of Veterinary Medicine, 1989)
The parotid salivary gland in one humped camel (camelus dromedarius) is located along the caudal edge of the ramus of mandible and on the masseter muscle. The gland has a long triangular outline and a red-brown color. The lateral surface is covered by parotid fascia and the cutaneous and parotido-auricularis muscles. It is bounded dorsally by zygomatico-auricularis muscle. The gland takes its blood supply from three branches which come from the facial artery that supply the middle and distal part of the gland, while the proximal part receives its blood supply from the superficial temporal and cranial temporal arteries. The parotid duct of the gland passes over the lateral surface of the masseter muscle, inferior to the orbital cavity and opens into the opposite 4th upper cheek tooth.